Resident Trainees Do Not Affect Patient Satisfaction in an Outpatient Gastroenterology Clinic: A Prospective Study Conducted in a Canadian Gastroenterology Clinic - Mayur Brahmania; Madison Young; Chetty Muthiah; Alexandra Ilnyckyj; Donald Duerksen; Dana C Moffatt (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: There is little literature regarding how a gastroenterology trainee affects a patient’s interpretation of care during outpatient clinic visits. Improving patient satisfaction is desirable and benefits may include enhanced patient compliance as well as providing trainees with areas for improvement.